Infective endocarditis following tumor necrosis factor-α antagonist therapy for management of psoriatic erythroderma: a case report. (December 2017) - Mizuno, Takuro; Kiyosawa, Jun; Fukuda, Akihiro; Watanabe, Seiji; Kurose, Nozomu; Nojima, Takayuki; Kanda, Tsugiyasu
Abstract Background The introduction of biological agents, such as infliximab, which act against tumor necrosis factor-α was a major advance for the treatment of an increasing number of chronic diseases. Tumor necrosis factor-α antagonists represent a major therapeutic advance for the management of chronic inflammatory diseases, such as psoriasis. Previous studies have reported that the use of tumor necrosis factor-α antagonists increased the risk of opportunistic infections and reactivation of latent bacterial infections. Cardiac involvement, such as infective endocarditis, is very rare in the literature. Case presentation A 77-year-old Asian man with a 10-year history of psoriatic erythroderma was referred due to high fever and general malaise. He was treated with Predonine (prednisolone) and infliximab. After treatment, cardiac echography showed mitral valve vegetation and brain magnetic resonance imaging indicated multiple fresh infarctions. He died from large brain infarction in October 2013. An autopsy showed fresh thrombosis in his left middle cerebral artery, mitral valve vegetations, and septic micro-embolisms in multiple organs. Conclusions Lethal bacterial endocarditis was revealed after administration of tumor necrosis factor-α inhibitor, infliximab, for the treatment of psoriatic erythroderma. An autopsy showed vegetation in his mitral valve and brain infarction with fresh purulent embolism in his left middle cerebral artery and septic micro-embolisms.